Equity valuation of PUMA SE - Krefting, Till (2023)
In this thesis, a valuation of the company “PUMA SE” is performed using suitable methods and, in dependence of the current share price, an investment recommendation is given to (potential) investors. As an established manufacturer in the sporting goods industry, PUMA operates in an attractive growth market due to superordinate social trends. Overall, the established players have enjoyed great popularity among investors in recent years. Despite positive outlooks, the entire industry face challenges in the near future due to macroeconomic factors. These must be overcome for a sustainable strategic positioning in the market. The author is confident that PUMA will succeed in taking the steps needed and, regardless of the valuation method chosen, he concludes that PUMA is currently undervalued and that a purchase of the share therefore makes sense. This is in line with the conclusion of the analyst of AlsterResearch AG, with whose equity report the results are compared at the end of the thesis.